2018
DOI: 10.1128/aem.01866-17
|View full text |Cite
|
Sign up to set email alerts
|

F-Specific RNA Bacteriophages, Especially Members of Subgroup II, Should Be Reconsidered as Good Indicators of Viral Pollution of Oysters

Abstract: Norovirus (NoV) is the leading cause of gastroenteritis outbreaks linked to oyster consumption. In this study, we investigated the potential of F-specific RNA bacteriophages (FRNAPH) as indicators of viral contamination in oysters by focusing especially on FRNAPH subgroup II (FRNAPH-II). These viral indicators have been neglected because their behavior is sometimes different from that of NoV in shellfish, especially during the depuration processes usually performed before marketing. However, a significant bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 61 publications
5
11
0
Order By: Relevance
“…Again, this difference could be explained by a higher growth rate for FRNAPH-I compared to FRNAPH-II, as previously reported (22). For example, for the same initial concentration of 0.5 PFU for both genogroups, Hartard et al (25) demonstrated that 57% of ICC-RT-qPCR detected FRNAPH-I against only 14% for FRNAPH-II. Because of the high rate of bacteriophage multiplication induced by this method, we recommend performing the analysis on four samples at a time to limit contamination risk.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…Again, this difference could be explained by a higher growth rate for FRNAPH-I compared to FRNAPH-II, as previously reported (22). For example, for the same initial concentration of 0.5 PFU for both genogroups, Hartard et al (25) demonstrated that 57% of ICC-RT-qPCR detected FRNAPH-I against only 14% for FRNAPH-II. Because of the high rate of bacteriophage multiplication induced by this method, we recommend performing the analysis on four samples at a time to limit contamination risk.…”
Section: Resultssupporting
confidence: 52%
“…When focusing only on purification conditions applied to oysters coming from polluted areas, many studies have shown not only the incidence of physicochemical conditions (i.e., water temperature, salinity, and dissolved oxygen) on shellfish physiology but also the effect of the initial microorganism load (i.e., natural or artificial contamination) (10,(35)(36)(37). For these reasons, we decided to work with naturally NoV-contaminated oysters that were also positive for FRNAPH, because of the high correlation previously demonstrated (25). The initial batch had been collected in winter and the high E. coli count observed (1,200 MPN/100 g of FIL) indicate a fecal contamination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sizes, shape structures, and genomes of FRNAPHs are similar to those of noroviruses [1,2], which have caused numerous outbreaks of gastroenteritis in multiple countries [3]. Furthermore, FRNAPH behavior, abundance, and survival in the environment including during water treatment are also similar to those of human enteric viruses [1,2,[4][5][6]. Thus, they serve as potential indicators of water contamination and the fates of viruses in aquatic environments and wastewater treatment plants (WWTPs) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%